Cognitive and Affective Empathy, Personal Belief in a Just World, and Bullying Among Offenders. Issue 17 (September 2017) - López-Pérez, Belén; Hanoch, Yaniv; Holt, Kayleigh; Gummerum, Michaela
Bullying extracts a heavy toll on offenders and prison staff alike. Studying what factors may affect bullying is extremely important as this may help to minimize bullying in prison. Although there is research on the relationship between lack of empathy and positive attitude toward bullying, previous research has overlooked that age may influence this relationship. In fact, previous research has shown that there are changes in empathy across the life span. Therefore, we examined whether having a positive attitude toward bullying in offenders was predicted by age, mediated by cognitive/affective empathy. Another important factor in the prediction of positive attitudes toward bullying may be the belief in a just world, as having a weak belief is related to more aggressive outbursts. Given that there is scarce research in the topic, we examined the relationship between having a positive attitude toward bullying and personal belief in a just world. To that aim, 123 sentenced adult male prisoners, selected from a Category C prison in the United Kingdom completed different questionnaires to assess their levels of cognitive and affective empathy, positive attitude toward bullying, and personal belief in a just world. As expected, age predicted a positive attitude toward bullying, mediated by affective empathy. However, we did not find a positive relationship between a positive attitude toward bullying and a personal belief in a just world. The results are discussed in terms of their application in possible intervention programs.